2020
DOI: 10.3390/brainsci10080545
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Multiple Disease-Related Protein Groups Induced by Valproic Acid in Human SH-SY5Y Neuroblastoma Cells

Abstract: Valproic acid (VPA) is a multifunctional medication used for the treatment of epilepsy, mania associated with bipolar disorder, and migraine. The pharmacological effects of VPA involve a variety of neurotransmitter and cell signaling systems, but the molecular mechanisms underlying its clinical efficacy is to date largely unknown. In this study, we used the isobaric tags for relative and absolute quantitation shotgun proteomic analysis to screen differentially expressed proteins in VPA-treated SH-SY5Y cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…SMARCA-deficiencies are associated to several malignancies and birth defects; its homozygous loss lead to embryo lethality (Pulice and Kadoch, 2016). Valproic acid is known to alter the expression of SMARCA4 and SMARCD1 in neuroblastoma cells (Hu et al, 2020), and SMARCA genes are suggested as members of the neurogenic transcriptional network control (Higgins et al, 2019). Hence, valproate-induced perturbances in SMARCA genes might be sufficiently disruptive to explain Fetal Valproate Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…SMARCA-deficiencies are associated to several malignancies and birth defects; its homozygous loss lead to embryo lethality (Pulice and Kadoch, 2016). Valproic acid is known to alter the expression of SMARCA4 and SMARCD1 in neuroblastoma cells (Hu et al, 2020), and SMARCA genes are suggested as members of the neurogenic transcriptional network control (Higgins et al, 2019). Hence, valproate-induced perturbances in SMARCA genes might be sufficiently disruptive to explain Fetal Valproate Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“… 112 In BD, studies have shown that E2 and E3 may be involved in the pathophysiology of the disorder. 113 , 114 UBE3A and CUL1 genes (coding for E3) are negatively expressed in the frontal cortex of BD subjects. 114 Valproic acid, frequently used as an antimanic agent in BD can induce differential expression of ANAPC4, CDC23, FBXO2, FBXO4, NEDD4, TRAF6, UBE2D1, UBE2E1, UBE2E3 and UBE2G2 , genes encoding E2 and E3 113 in human neuroblastoma cells.…”
Section: Ubiquitin and Proteasome System Dysfunction In Mood Disordersmentioning
confidence: 98%
“…An enrichment analysis of gene-disease associations was performed using the DisGeNET database [54]. RT-qPCR assays were performed using the comparative ∆∆Ct method to validate the differential gene expression [55]. The expression levels of GRIK1, GRIK2, GRIK3, GRIK4, GRIK5, GRIA2, GRIA4, GABRB3, GRM8, and KCNJ3 were assayed using the QuantStudio 3 real-time PCR system in combination with continuous SYBR Green detection (ThermoFisher Scientific Inc.).…”
Section: Human Cell Line Identificationmentioning
confidence: 99%